The impact of occlusal morphology on fissure sealant penetration - Petrović Bojan; Marković Dejan; Blagojević Duška (Serbian Medical Society - Dental Section, Belgrade, 2006)
Introduction: In contemporary preventive dentistry there are numerous experimental in vitro and clinical studies on the growing number of materials for sealing pits and fissures. Aim: the aim of this study was to evaluate the impact of occlusal tooth morphology on penetrating abilities of two types of fissure sealants and measure the unfilled space at the bottom of occlusal groove using scanning electron microscopy (SEM). Materials and methods: The sample consisted of 10 freshly extraced intact premolars and 10 molars randomly divided into 4 groups. In group I (5 premolars), and group II (5 molars) glass ionomer Fuji VII was used as fissure sealant, while in groups III (5 premolars) and IV (5 molars) resin-based sealant (Helioseal-F) was used. Six sections of each tooth were prepared for SEM. Sealant penetration was observed at 30x magnification and the unfilled space at the bottom of the groove at 500x. Sealant penetration in relation to the absolute depth of occlusal grooves was recorded and the unfilled space beneath the sealant was expressed through its greatest diameter. Results were statistically analyzed using χ2 test. Results: There was no statistically significant difference in penetration ability and the unfilled space between tested materials or teeth groups. The average depth of penetration for glass ionomer was 83% and for resin-based sealant 81% of fissure depth. Mean diameters of the unfilled space beneath the sealants were 95 μm (glass ionomer) and 93 μm (resin-based sealant). Shallower penetration of both sealing materials was observed in deep pits and fissures with greater diameter of unfilled space (p<0.05). Conclusion: Based on results of the present study it can be concluded that penetration of contemporary fissure sealants largely depends on occlusal tooth anatomy.